Interrelation Features of Mental States and Interpersonal Relations of Children with the Teacher - Svetlana G. Krasnova (Развитие образования, 2019)
The article is devoted to the identification of interrelations between mental states and interpersonal relations of children with the teacher in the group of preschool educational institution. The relevance of the study is out of question, since the definition of the interrelation features of mental states and interpersonal relations of children with the teacher is significant in understanding the mechanisms of children’s development in ontogenesis and it is associated with the study of the factors of child’s formation as a person and his socialization. Methods: psychodiagnostic methods, adequate research objectives, methods of statistical processing of experimental data (criterion r-Pearson linear correlation coefficient, cluster analysis) were applied. Research results. The article presents the results of relational and cluster analysis. Based on the results of the cluster analysis, the typological differentiation of the teacher's relations with children is developed. The dendrogram of relations types of teachers with children allowed to identify the following types: authoritative, controlling, emotionally-patronizing, dominating, formal. The correlation analysis allowed to reveal interrelation features of relations types of the teacher with children and mental states. The analysis of correlations allowed to allocate through and special, characteristic only for a certain age stage of development, negative and positive mental states of preschoolers. conclusion. It is found that the authoritative position of the teacher in relations with preschoolers causes high-energy positive mental states. Negative states of high level of activity are manifested depending on the controlling and dominant types of relations. Psychical states of low energy level are associated with emotional-patronizing type of relationship.